Work Environment and Work Stress: The Mediating Role of Job Satisfaction in a State-Owned Pharmaceutical Company - Nadiya Yusriyyah; Rina Novianty (Journal of Educational Management Research, 2026)
This study examined whether the work environment influences work stress directly and indirectly through job satisfaction at PT Bio Farma (Persero). Rising stress scores and concentration problems indicated psychosocial risks within this pharmaceutical setting. Identifying manageable organizational determinants is essential for employee well-being and operational reliability. A cross-sectional explanatory design involved 170 employees selected through stratified sampling across seven directorates. Data were collected using Likert questionnaires and analyzed with PLS-SEM in SmartPLS 4.0. Employees reported a high work environment score (3.61), high job satisfaction (3.55), and moderate work stress (2.62). The measurement model demonstrated reliability and convergent and discriminant validity. The work environment negatively influenced work stress (β = −0.334, p < .001). It positively influenced job satisfaction (β = 0.482, p < .001). Job satisfaction negatively influenced work stress (β = −0.394, p < .001). Job satisfaction partially mediated the work environment–stress relationship through an indirect effect (β = −0.190, p < .001). The findings support a resource-based explanation of stress in pharmaceutical operations. Management should improve lighting, grievance mechanisms, career development, promotion transparency, rest quality, and support for concentration.